IMPORTANCE OF EARLY WARNING SYSTEMS IN IDENTIFYING RISK - Khudoyberdiyev Javharbek; Izbosarov Boburjon (American Journals, 2023)
The article provides information on the importance of early warning systems for identifying risks in commercial banks of the Republic of Uzbekistan, as well as what early warning indicators can be used, types of risks, their classification, theoretical mechanisms for their assessment and minimization in the field of investment and business are presented. Also, this article presents the opinions of foreign and domestic scientists about the risks.
Keywords: early warning system, early warning indicator, risk, credit risk, risk management strategy.